2010
DOI: 10.5194/acp-10-12091-2010
|View full text |Cite
|
Sign up to set email alerts
|

Global ozone monitoring by occultation of stars: an overview of GOMOS measurements on ENVISAT

Abstract: Abstract. GOMOS on ENVISAT (launched in February, 2002) is the first space instrument dedicated to the study of the atmosphere of the Earth by the technique of stellar occultations (Global Ozone Monitoring by Occultation of Stars). Its polar orbit makes good latitude coverage possible. Because it is self-calibrating, it is particularly well adapted to long time trend monitoring of stratospheric species. With 4 spectrometers, the wavelength coverage of 248 nm to 942 nm enables monitoring ozone, H 2 O, NO 2 , N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 91 publications
0
104
0
Order By: Relevance
“…To achieve this goal, ground-based, balloon-borne, airborne and satellite instruments have been used to monitor ozone abundances in the atmosphere during the last decades. For satellite instruments, different observation techniques including solar/stellar occultation measurements (e.g., SAGE -Stratospheric Aerosol and Gas Experiment (McCormick et al, 1989); HALOE -Halogen Occultation Experiment (Russell et al, 1994); ACE -Atmospheric Chemistry Experiment (McElroy et al, 2007); GOMOSGlobal Ozone Monitoring by Occultation of Stars (Bertaux et al, 2010)), limb scatter/emission measurements (e.g., MLS -Microwave Limb Sounder (Waters et al, 2006); MIPAS -Michelson Interferometer for Passive Atmospheric Sounding (Fischer et al, 2008); OSIRIS -Optical Spectrograph and InfraRed Imager System (Llewellyn et al, 2004)) and nadir measurements (e.g., GOME/GOME2 -Global Ozone Monitoring Experiment Callies et al, 2000); OMI -Ozone Monitoring Instrument (Levelt et al, 2006); IASI -Infrared Atmospheric Sounding Interferometer (Clerbaux et al, 2009)) are used (see, e.g., Sofieva et al, 2013;Hassler et al, 2014, and references therein). The passive imaging spectrometer used in this study, SCIA-MACHY (SCanning Imaging Absorption spectroMeter for Atmospheric CartograpHY), provided vertical distributions of atmospheric trace gases by employing the limb-scattering measurement technique (Burrows et al, 1995;Bovensmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, ground-based, balloon-borne, airborne and satellite instruments have been used to monitor ozone abundances in the atmosphere during the last decades. For satellite instruments, different observation techniques including solar/stellar occultation measurements (e.g., SAGE -Stratospheric Aerosol and Gas Experiment (McCormick et al, 1989); HALOE -Halogen Occultation Experiment (Russell et al, 1994); ACE -Atmospheric Chemistry Experiment (McElroy et al, 2007); GOMOSGlobal Ozone Monitoring by Occultation of Stars (Bertaux et al, 2010)), limb scatter/emission measurements (e.g., MLS -Microwave Limb Sounder (Waters et al, 2006); MIPAS -Michelson Interferometer for Passive Atmospheric Sounding (Fischer et al, 2008); OSIRIS -Optical Spectrograph and InfraRed Imager System (Llewellyn et al, 2004)) and nadir measurements (e.g., GOME/GOME2 -Global Ozone Monitoring Experiment Callies et al, 2000); OMI -Ozone Monitoring Instrument (Levelt et al, 2006); IASI -Infrared Atmospheric Sounding Interferometer (Clerbaux et al, 2009)) are used (see, e.g., Sofieva et al, 2013;Hassler et al, 2014, and references therein). The passive imaging spectrometer used in this study, SCIA-MACHY (SCanning Imaging Absorption spectroMeter for Atmospheric CartograpHY), provided vertical distributions of atmospheric trace gases by employing the limb-scattering measurement technique (Burrows et al, 1995;Bovensmann et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…FWHM increased from 2.7 BU to 7.4 BU. A widening of the dark current distribution was also noticed for OMI (Schenkeveld et al, 2017) and GOMOS (Bertaux et al, 2010).…”
mentioning
confidence: 73%
“…This is comparable to earlier work by Dehn (2003) and our predecessor study (Coldewey-Egbers et al, 2008) as well as to Munro et al (2016) who analyzed the dark signal for the GOME-2 instrument on-board the MetOp series of satellites using the same type of detectors. For OMI, which 5 is a nadir viewing UV-VIS imaging spectrograph using two-dimensional charge-coupled device (CCD) detectors Dobber et al, 2006), a 7-fold dark current increase was found from 2005 to 2015 (Schenkeveld et al, 2017), and for GOMOS/ENVISAT (Global Ozone Monitoring by Occultation of Stars) -using the same CCD detectors as OMI an even higher increase was found (Bertaux et al, 2010). Although the increase in the dark current seems to be significant, there is not necessarily a negative impact on the quality of the level 1 data products as long as appropriate dark current measurements are 10 available and applied during the level 0-to-1 processing.…”
mentioning
confidence: 97%
“…Bertaux et al, 2010). Shortly, GOMOS was embarked on board the ENVISAT platform launched in 2002 in a heliosynchronous circular orbit at an altitude of 800 km.…”
Section: Gomos Instrumentsmentioning
confidence: 99%